2018
DOI: 10.1016/j.bbadis.2018.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Biglycan gene connects metabolic dysfunction with brain disorder

Abstract: Dietary fructose is a major contributor to the epidemic of diabetes and obesity, and it is an excellent model to study metabolic syndrome. Based on previous studies that Bgn0/− gene occupies a central position in a network of genes in the brain in response to fructose consumption, we assessed the capacity of (Bgn0/−) to modulate the action of fructose on brain and body. We exposed male biglycan knockout mice (Bgn0/−) to fructose for 7 weeks, and results showed that Bgn0/− mice compensated for a decrement in le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…In this study, no changes in the phosphorylation of AKT and FoxO1 were at the time points where the NPY and POMC were changed by BGN treatment in N41 and N43/5. One study using transcriptome profiling reported that the signaling pathways related to oxidative phosphorylation, glucose and lipid metabolism, and neurotrophin were highly altered in the hypothalamus of Bgn knockout mice 32 . The data showing differentially expressed genes and pathways in the hypothalamus by Bgn knockout might be helpful to find candidates responsible for BGN‐mediated regulation of hypothalamic neuropeptide expression for future studies.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this study, no changes in the phosphorylation of AKT and FoxO1 were at the time points where the NPY and POMC were changed by BGN treatment in N41 and N43/5. One study using transcriptome profiling reported that the signaling pathways related to oxidative phosphorylation, glucose and lipid metabolism, and neurotrophin were highly altered in the hypothalamus of Bgn knockout mice 32 . The data showing differentially expressed genes and pathways in the hypothalamus by Bgn knockout might be helpful to find candidates responsible for BGN‐mediated regulation of hypothalamic neuropeptide expression for future studies.…”
Section: Discussionmentioning
confidence: 98%
“…One study using transcriptome profiling reported that the signaling pathways related to oxidative phosphorylation, glucose and lipid metabolism, and neurotrophin were highly altered in the hypothalamus of Bgn knockout mice. 32 The data showing differentially expressed genes and pathways in the hypothalamus by Bgn knockout might be helpful to find candidates responsible for BGN-mediated regulation of hypothalamic neuropeptide expression for future studies. While the exact mechanism responsible for the modulation of neuropeptide expression by BGN treatment remains unclear, it is also unknown whether BGN can cross blood-brain barrier (BBB).…”
Section: Discussionmentioning
confidence: 99%
“…The second category is Bayesian networks that can flexibly incorporate various types of prior information such as genetic causality, genetic regulation of gene expression (expression quantitative trait loci or eQTLs), transcription factor binding, and epigenetic regulatory information to model directional but sparse regulatory networks [75][76][77][78][79][80]. Combination of these two types of networks is particularly powerful in revealing novel mechanistic insights, as one offers a global view of gene co-regulation and the other provides sparse but directional granular regulatory relations to elucidate many different contributors to disease pathogenesis [75][76][77][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96].…”
Section: How To Determine What Type Of Network To Usementioning
confidence: 99%
“…It has been reported that abiraterone could inhibit the expression of several drug-metabolizing cytochrome P450 enzymes, including CYP2D6 (36,37). Ying et al have demonstrated that as a key modulator, BGN regulates the key molecular pathways of metabolism and brain function (38). Yuan et al reported that BGN, a proteoglycan of the ECM, was identified as a fibroblast-specific biomarker of poorer prognosis in colorectal cancer (39).…”
Section: Discussionmentioning
confidence: 99%